Developing ozone-tolerant rice (Oryza sativa L.) through marker-assisted breeding for enhancing food security in air-polluted environments - Alam, Muhammad Shahedul; Justus Liebig University Giessen (My University, 2025)
Environmental stressors, particularly tropospheric ozone (O₃), which significantly reduces crop yields, are increasingly threatening global food security. Rice (Oryza sativa L.), a staple food for more than half of the world’s population, is highly vulnerable to ozone stress. Chronic exposure to ozone results in reduced photosynthesis, accelerated senescence, and significant yield losses. This study aimed to develop ozone-tolerant rice varieties through marker-assisted breeding, focusing on two quantitative trait loci (QTLs), OzT8 and OzT9, known for conferring ozone tolerance. The research was conducted in four phases. The first phase investigated the interactive effects of ozone stress and blast disease (Magnaporthe oryzae) on different rice genotypes under controlled greenhouse conditions. Physiological measurements—including spectral reflectance indices, gas exchange parameters, biochemical analysis, and yield data—revealed that ozone exposure reduced blast disease severity. However, blast infection did not significantly affect the sensitivity of rice to ozone. While breeding for ozone tolerance had long been hindered by concerns about potential trade-offs with disease resistance, this study provided confidence that breeding for both traits is feasible. In the second phase, marker-assisted backcross breeding was employed to introgress OzT8 and OzT9 from the donor parent Kasalath into two ozone-sensitive Bangladeshi rice varieties, BRRI dhan28 and Binadhan-11. Successive generations of genotypic and phenotypic selection resulted in the development of breeding lines homozygous for the tolerant alleles. Subsequently, 77 breeding lines harboring OzT8 and/or OzT9 were evaluated in a greenhouse experiment. These lines were assessed for key physiological traits—such as stomatal conductance, chlorophyll fluorescence, nitrogen balance index—and agronomic traits, including grain yield and biomass accumulation. Several lines demonstrated enhanced ozone tolerance, improved photosynthetic efficiency, reduced lipid peroxidation, and superior yield performance compared to their parental lines. In the third and fourth phases, comprehensive greenhouse and field trials were conducted to confirm the performance of the selected breeding lines. Physiological traits (e.g., nitrogen balance index, stomatal conductance, chlorophyll fluorescence) and agronomic traits (e.g., grain yield, harvest index) were thoroughly analyzed. Results validated the superior performance of breeding lines containing both OzT8 and OzT9, with several lines showing significant yield improvements under ozone stress conditions. This study highlights the potential of marker-assisted breeding in developing ozone-tolerant rice varieties, offering a promising solution to mitigate ozone-induced yield losses and improve rice production in air-polluted regions. It concludes with a recommendation for multi-location trials to validate the stability of ozone tolerance across diverse environments and to explore the integration of additional QTLs for greater genetic diversity and broader adaptation.
Keywords: Ozone tolerance; Marker-assisted breeding; Quantitative trait loci; Rice; Food security; ddc:630